Penyuluhan Anemia dan Pemberian Tablet Tambah Darah pada Remaja Putri: Anemia Education and Provision of Iron Supplement Tablets for Adolescent Girls - Marselina, Marselina; Rau, Muh. Jusman; Buchair, Hikmah; Rahmania, Rahmania; Umar, Mutmainnah; Simbaju, Deiske; Hartini, Diah Ayu (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
One of the health problems in developing countries, including Indonesia, is nutritional problems such as micronutrient deficiencies such as anemia. Anemia is a condition in the body where the blood's hemoglobin (Hb) level is lower. The prevalence of anemia in Indonesia is still quite high at 48.9%, with the proportion of anemia in the age group 15-24 years and 25-34 years, an increase in cases in adolescent girls, namely 37.1% in 2013 to 48.9% in 2018. Based on these problems, community service activities through anemia counseling activities and the provision of iron supplement tablets to young women are carried out to increase young women's knowledge regarding anemia. This activity was carried out at SMA Negeri 4 Palu with 34 participants consisting of students from class X and XI, using lecture and discussion methods using PowerPoint and leaflet media. The measurement of service results showed a significant difference between the pretest and posttest groups, with the posttest scores being higher than the pretest scores and an increase in the average value from pretest to posttest scores. So, it can be concluded that there was an increase in knowledge of the participants after being given counseling. Achieving the goal of service is expected to increase understanding regarding the importance of educational efforts as an effort to prevent and overcome health problems through improving knowledge.